SITUS-SITUS “TERSEMBUNYI” MASA KLASIK DI KABUPATEN SEMARANG, JAWA TENGAH - Sugeng Riyanto (Berkala Arkeologi, 2013)
Archaeological data of classical period in Semarang Regency has been "underestimated" in archaeological research as an area of Ancient Mataram period because the region is situated "outside" the Kedu – Prambanan axis, except the Gedongsongo and Ngempon temples. It’s convinced that in this region the others archaeological data are still covered as well. These sites are still "hidden" and there's a time to be revealed as part of Ancient Mataram civilization. The urge to uncover traces of civilization is manifested in an archaeological survey for acquiring of classical period data in Semarang Regency. This article reflects the results of the survey and has been set in an explanation of "hidden” sites from the classical period in Semarang Regency. This focused on two things, their archaeological potency and also the configuration of space based on its distribution.